1965
DOI: 10.1302/0301-620x.47b4.678
|View full text |Cite
|
Sign up to set email alerts
|

The Etiology and Prevention of Functional Instability of the Foot

Abstract: Functional instability of the foot (a term used in this paper to designate the disability to which patients refer when they say that their foot tends to " give way ") follows about 40 per cent of injuries to the lateral ligament of the ankle (Bosien, Staples and Russell 1955 ; Freeman THE JOURNAL OF BONE AND JOINT SURGERY THE ETIOLOGY AND PREVENTION OF FUNCTIONAL INSTABILITY OF THE FOOT 679 MATERIAL (Tables I and II) Eighty-five patients presenting consecutively at the Casualty Department of Westminster Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
477
4
50

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 829 publications
(542 citation statements)
references
References 4 publications
11
477
4
50
Order By: Relevance
“…This finding may have significant implications for clinical practice as unstable surfaces do not seem to target proprioceptive training of ankle musculature. Freeman et al (1965) were the first to design a functional ankle rehabilitation program based on the premises that proprioception deficits have a causal effect on re-injury. They state that mechanoreceptors in the lateral ankle ligaments (among other receptors) control the precise contractions of the calf muscles which must occur if the foot is to remain stable on uneven ground.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may have significant implications for clinical practice as unstable surfaces do not seem to target proprioceptive training of ankle musculature. Freeman et al (1965) were the first to design a functional ankle rehabilitation program based on the premises that proprioception deficits have a causal effect on re-injury. They state that mechanoreceptors in the lateral ankle ligaments (among other receptors) control the precise contractions of the calf muscles which must occur if the foot is to remain stable on uneven ground.…”
Section: Discussionmentioning
confidence: 99%
“…They state that mechanoreceptors in the lateral ankle ligaments (among other receptors) control the precise contractions of the calf muscles which must occur if the foot is to remain stable on uneven ground. A traction injury will lead to the rupture of nerve fibers as well as of collagen fibers (Freeman et al 1965). If the ligaments heal in an elongated state, the mechanoreceptors will misinterpret the inversion angle (Konradsen 2002).…”
Section: Discussionmentioning
confidence: 99%
“…So it seems that balance training can be an efficient tool to prevent injury. It has been shown that balance training helps to regenerate neuromuscular structures after injuries (Eils & Rosenbaum, 2001;Freeman, Dean, & Hanham, 1965) and also helps to prevent recurrence (Mcguine & Keene, 2006;Verhagen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of COP and joint position sense in university soccer players with and without ankle instability mechanoreceptors joints become damaged, impairing particularly the joint position sense, resulting in a situation known as the functional ankle instability (FAI) [14][15][16] , which is de ned by F 17 as a complain of "false subjective perception". H 18 attributed its causes to de cits in the joint position sense, reduced muscle strength, delay in bular muscles activation, equilibrium de cits, alterations in the activity of the bular nervous and decrease in the dorsi exion range of the movement, and its residuals symptoms may remain for long periods 19 .…”
Section: Introductionmentioning
confidence: 99%